Double Differential Cross-Sections for Electron Impact Ionization of Atoms and Molecules - Mevlut Dogan; Melike Ulu; Zehra Nur Ozer; Murat Yavuz; Gulin Bozkurt (Journal of Spectroscopy)
The single ionizing collision between an incident electron and an atom/molecule ends up two kinds of outgoing electrons called scattered and ejected electrons. As features of electron impact ionization, these two types of electrons are indistinguishable. Double differential cross-sections (DDCS) can be obtained by measuring the energy and angular distributions of one of the two outgoing electrons with an electron analyzer. We used He, Ar, H2, and CH4 targets in order to understand the ionization mechanisms of atomic and molecular systems. We measured differential cross-sections (DCS) and double differential cross-sections at 250 eV electron impact energy. The elastic DCSs were measured for He, Ar, H2, and CH4, whereas the inelastic DCSs of He were obtained for 21P excitation level for 200 eV impact electron energy.